Yahoo 知識+ 將於 2021 年 5 月 4 日 (美國東岸時間) 停止服務,而 Yahoo 知識+ 網站現已轉為僅限瀏覽模式。其他 Yahoo 資產或服務,或你的 Yahoo 帳戶將不會有任何變更。你可以在此服務中心網頁進一步了解 Yahoo 知識+ 停止服務的事宜,以及了解如何下載你的資料。

integrate following expressions?

It's a question from physics (system dynamics), but essentially its some basic math. (L is a constant, omega is angular speed, also constant), x is derived by t, ie time.

x'' = (7*L/12) * [omega]^2 * cos([omega]*t)

all starting conditions were 0 (x'_o= 0, x_o=0 - starting speed and position were 0)

The answer should be x = (7*L/12) * (1- cos([omega]*t)). I need the steps in between.

2nd question (C is const)

x'' = C * (r* [omega]^2 /4 )* sin ([omega] *t/2)

answer is

x = C * (r* [omega]t /2 - r* sin ([omega] *t/2)

and I need the steps in between.

4 個解答

相關度
  • 10 年前
    最愛解答

    (1) Given, x"(t) = (7Lω^2/12) Cosωt ; Integrating once, we get

    x' (t) = (7Lω^2/12) ∫Cosωt dt = (7Lω/12) ∫Cosωt (ωdt) [θ = ωt , dθ = ωdt]

    = (7Lω/12) Sinωt + k ; when t = 0, x'(0) = 0 => k = 0

    Hence x'(t) = (7Lω/12) Sinωt ; Integrating again, we get

    x(t) = (7Lω/12) ∫Sinωt dt = (7L/12) ∫Sinωt (ωdt) ; [θ = ωt , dθ = ωdt]

    = (7L/12)*(- Cosωt) + k' ; when t = 0, x(0) = 0 => 0 = - (7L/12) + k' => k' = (7L/12)

    Hence x(t) = (7L/12) {1 - Cosωt}

    (2) Given, x"(t) = (C r ω^2 / 4) Sin(ωt/2) ; Integrating once, we get

    x'(t) = (C r ω^2 / 4) ∫Sin(ωt/2) dt = (C r ω / 2) ∫Sin(ωt/2) (ωdt/2) ; [θ = ωt/2 , dθ = ωdt/2]

    = (C r ω / 2)*{- Cos(ωt/2)} + k ; when t = 0, x'(0) = 0 => k = (C r ω / 2)

    Hence, x'(t) = (C r ω / 2)*{1 - Cos(ωt/2)} ; Integrating again, we get

    x(t) = (C r ω / 2)*∫{1 - Cos(ωt/2)} dt = (Cr)*∫{1 - Cos(ωt/2)} (ωdt/2) ; [θ = ωt/2 , dθ = ωdt/2]

    x(t) = (Cr)*{(ωt/2) - Sin(ωt/2)} + k" ; when t = 0, x(0) = 0 => k" = 0

    Hence x(t) = C*{r*(ωt/2) - r*Sin(ωt/2)}

  • SS4
    Lv 7
    10 年前

    x''(t) = 7ω²L/12 * cos(ωt)

    x'(t) = 7ωL/12 * sin(ωt) + C

    We are told x'(0) = 0 so x'(0) = 7ωL/12 * sin(0) +C = 0 --> C=0

    x'(t) = 7ωL/12 * sin(ωt)

    x(t) = -7L/12 cos(ωt) + C' (where C' is also a constant)

    At t=0, x(t) = 0 and so -7L/12 + C' = 0 therefore C' = 7L/12

    x(t) = -7L/12 cos(ωt) + 7L/12 = 7L/12 - 7L/12 cos(ωt) = 7L/12(1-cos(ωt))

  • 4 年前

    first one is 0.5x^4- x^3 + 2.5x^2 -2x + C 2d one is -2.5cos(2?) + 0.5 sin(4?) + C to the guy above: in case you do not recognize then get yahoo solutions violation of -10 factors

  • For a harmonic function:

    x(t) = k∙cos(wt)

    dx/dt = -kw∙sin(wt)

    d²x/dt² = -kw²∙cos(wt) = -w² x(t)

    The answer should be x = (7*L/12) * (-cos([omega]*t))

    The answer should be x = C * r * (-sin([omega]*t/2))

還有問題嗎?立即提問即可得到解答。